Large‐scale phylogenetic analysis provides insights into the diversification and evolution of sessilid peritrich ciliates (Protista: Ciliophora). (17th October 2022) - Wang, Xueyan; Jiang, Chuanqi; Gu, Siyu; Liu, Zhencheng; Xiong, Jie; Warren, Alan; Miao, Wei
Abstract: The Peritrichia is a speciose and morphologically distinctive assemblage of ciliated protists that was first observed by Antonie van Leeuwenhoek over 340 years ago. In the last two decades, the phylogenetic relationships of this group have been increasingly debated as morphological and molecular analyses have generated contrasting conclusions, mainly owing to limited sampling. In the present study, we performed expanded phylogenetic analyses of 152 sessilid peritrichs collected from 14 different provinces of China and 141 SSU rDNA peritrich sequences from GenBank. The results of the analyses revealed new divergent relationships between and within major clades that challenge the morphological classification of this group including, (1) the recovery of four major phylogenetically divergent clades in the monophyletic order Sessilida, (2) aboral structures such as the stalk and spasmoneme were evolutionary labile, (3) the stalk or/and spasmoneme was lost in each divergent clade indicating that parallel evolution occurred in sessilid peritrichs and (4) the life cycle and habit drive the diversity of aboral structures as well as diversification and evolution in peritrichs.